KEWENANGAN PEMERINTAH DAERAH DALAM PENGELOLAAN RETRIBUSI PARIWISATA DI KABUPATEN MINAHASA UTARA - Dumanaw, Trevina (LEX ET SOCIETATIS, 2015)
The purpose of this study is to determine how the tourism levy based management regulations minahasa northern district No. 6 of 2011 on levies and how the local authorities in the north Minahasa district management with tourism levy. With normative methods concluded that; 1. Regional Regulation No. 6 of 2011 on Levies force in North Minahasa Regency sinkroon until now no longer with the application of the levy rates in the field of tourism. Need to change and revision back law No. 6 of 2011 is. 2. Management of the tourism levy in North Minahasa Regency should bring a clear impact for the community. When the government appealing to the community levy of course there are services that are provided directly. They should benefit society is to be able to enjoy the services provided by the government for what has been paid community. Management of tourism levy be entirely local authority should be seen fully from the area of ââfinancial management. Is the overall financial management activities including planning, implementation, administration, reporting, accountability, and oversight of local finance. Kata Kunci : Retribusi Pariwisata